Clinical features and toxicity of tuberculosis treatment in patients with cancer - Luis Cuéllar; Carlos A. Castañeda; Katerin Rojas; Claudio Flores; Ketty Dolores-Cerna; Miluska Castillo; William Vicente (Revista Peruana de Medicina Experimental y Salud Pública, 2015)
Objectives. To assess the clinical and epidemiological characteristics of active tuberculosis in patients with malignancy and to assess the influence of TB treatment on cancer management at the National Institute of Neoplastic Diseases from 2008 to 2013. Materials and methods. Observational study of TB cases diagnosed by positive sputum microscopy in patients with cancer. Clinical information, evolution, and pathologic information of neoplasia was reviewed. Results.76 cases of active tuberculosis after being diagnosed with cancer were found. The median age was 51.3 years. Median follow-up was 2.1 years. The most common cancers were acute lymphocytic leukemia (14.5%), for the hematologic cancers; and cancer of the cervix (14.5%), breast (10.5%), and gastric (7.9%) for non-hematological cancers. 27.6% of patients had recurrence of the tumor; TB diagnosis confounded the initial staging by 6.9% and was initially stated as cancer recurrence in 11.1% (breast and colon cancers). The diagnosis of tuberculosis delayed or influenced the dose reduction of the antineoplastic treatment in 11.1% of the cases (acute lymphocytic leukemia and non-Hodgkin lymphoma). 8.3% of patients had toxicity to the TB treatment. Conclusions. Cancer patients may have active tuberculosis infection. The interference effect of diagnosis and treatment of tuberculosis on the assessment of cancer and cancer treatment in our series is minimal.